A comparative study energy consumption and costs of battery electric vehicle transmissions. (1st March 2016) - Ruan, Jiageng; Walker, Paul; Zhang, Nong
Highlights: Single reduction, DCT and CVT based battery electric vehicle models are compared. Shifting schedules for two-speed DCT and simplified CVT are optimized. Up to 14% motor efficiency improvements and 15% energy saving are achieved. Improvement results in multi-speed BEVs are experimentally validated. Initial manufacturing cost, lifetime daily use and maintenance cost are presented. Abstract: Despite the long-term benefit of battery electric vehicles (BEVs) to customers and environment, the initial cost and limited driving range present significant barriers for wide spread commercialization. The integration of multi-speed transmissions to BEVs' powertrain systems in place of fixed ratio reduction transmissions is considered as a feasible method to improve powertrain efficiency and extend limited driving range for a fixed battery size. The aim of this paper is to enable the researchers or BEV manufacturers, especially for transmission systems, to estimate whether their products are worthwhile for the customer in terms of the price/performance relationship of others' design solutions. To do so a generic battery electric vehicle is modelled in Matlab/Simulink® to predict motor efficiency and energy consumption for single reduction, two speeds Dual Clutch Transmission (DCT) and simplified Continuous Variable Transmission (CVT) equipped battery electric vehicles. A credible conclusion is gained, through experimental validation of single speed and two speeds DCT scenarios and reasonable assumptions to support the CVT scenario, that both two speeds DCT and simplified CVT improve the overall powertrain efficiency, save battery energy and reduce customer costs. However, each of the configurations has unique cost and energy consumption related trade-offs.